Aminolysis of epoxides catalyzed by three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Catalysis, 2012)
The application of three-dimensional, mesoporous titanosilicates (Ti-SBA-12 and Ti-SBA-16) as reusable, solid catalysts for the synthesis of a range of beta-amino alcohols in high yields and selectivity through ring-opening of epoxides with amines at ambient and solvent-free conditions is reported, for the first time. These mesoporous titanosilicates (Si/Ti = 20-80) were prepared by a direct hydrothermal synthesis route adjusting the concentration of HCl (0.05-2 M) used in the synthesis. Ti ions in these catalysts were mostly substituted for Si in the framework. Water adsorption and Si-29 magic-angle spin nuclear magnetic resonance spectroscopy revealed that Ti-SBA-16 is more hydrophobic than Ti-SBA-12. Mesoporosity, three-dimensional architecture, surface hydrophobicity and easy access of Lewis acidic, framework-substituted Ti sites are the factors responsible for the superior activity of Ti-SBA-16 compared to Ti-SBA-12 and the hitherto known solid catalysts for this reaction. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Aminolysis of epoxides; beta-Amino alcohol; Mesoporous titanosilicates; Molecular sieves; Ring opening of epoxides with amines; Ti-SBA-12; Ti-SBA-16